Multiplex TaqMan qPCR assay for specific identification of encapsulated Trichinella species prevalent in North America - de Almeida, Marcos (Mem Inst Oswaldo Cruz, 2018)
BACKGROUND Human trichinellosis is a foodborne parasitic zoonotic disease caused by ingestion of raw or undercooked meat infected with nematode larvae of the genus Trichinella. In the USA, sporadic cases and outbreaks caused by the consumption of wild game meat infected with Trichinella have been reported. The current methods for diagnosis such as serology and microscopy are not specific, may result in false negative results, and cannot differentiate encapsulated Trichinella larvae to species level. The molecular protocols currently available for the differentiation of all encapsulate Trichinella species prevalent in North America have some limitations such as the inability to identify and resolve the presence of several Trichinella species in a single test. OBJECTIVES/METHODS In this study we developed and evaluated a multiplex TaqMan quantitative real-time polymerase chain reaction (qPCR) assay, which can simultaneously detect, identify and differentiate all species of encapsulated Trichinella occurring in North America i.e., T. nativa, T. spiralis, T. murrelli and Trichinella T6, even in cases of multiple infection in a single sample. We investigated two human biopsies and 35 wild animal meat samples considered as having a high likelihood of harboring Trichinella larvae obtained from the United States during 2009-2017. FINDINGS Using the multiplex assay describe here, 22 (59%) samples that tested positive contained Trichinella spp., were identified as: T. nativa (n = 7, including a human biopsy), T. spiralis (n = 9, including a human biopsy), T. murrelli (n = 3), Trichinella T6 (n = 1). Results also included two rare mixed infection cases in bears, a T. nativa/T. spiralis from Alaska and a T. spiralis/Trichinella T6 from California. The species identifications were confirmed using a conventional PCR targeting the rRNA ITS1-ITS2 region, followed by DNA sequencing analysis. The estimated limit of detection (LOD) was approximately seven larvae per gram of meat. MAIN CONCLUSIONS Differentiation of Trichinella spp. is needed to improve efforts on identification of case, optimize food safety control and better understand the geographic distribution of Trichinella species. The Trichinella qPCR multiplex proved to be a robust, easy to perform assay and is presented as an improved technique for identification of all known encapsulated species occurring in North America continent.